ZIF-67 filled PDMS mixed matrix membranes for recovery of ethanol via pervaporation - Khan, A. (Elsevier B.V., 2018)
Zeolitic imidazole frameworks (ZIFs), a subclass of metal organic frameworks (MOFs), are composed of metal ions linked by organic ligands which offer an exceptionally high surface area and appealing separation potential. In this study, mixed matrix membranes (MMMs) were prepared using polydimethylsiloxane (PDMS) as a hydrophobic polymer and ZIF-67 as inorganic filler particle. ZIF-67 particles and MMMs were characterized by XRD, SEM, FTIR, BET and contact angle measurements. The prepared membranes were tested for the separation of ethanol/water mixtures via pervaporation. Compared to unfilled PDMS membranes, MMMs loaded with 20 wt ZIF-67 showed an increase in flux and a doubled separation factor. The easy synthesis of ZIF-67 and its enhanced separation performance make ZIF-67 an attractive candidate to prepare MMMs for a variety of membrane applications. Â© 2018 Elsevier B.V.